Weight Reduction of C-Drone Body Structure - Sarif, Muhammad Iqmal; Ramli, Muhammad Faiz; Mohd Saleh, Siti Juita Mastura (Progress in Aerospace and Aviation Technology, 2023)
Drones are becoming an increasingly useful tool to deliver parcels faster, greener and cheaper than previously inaccessible places. The purpose of this research work is to reduce the weight of the C-Drone main body structure. Therefore, tensile tests on Aluminium 6061 are reviewed to obtain the actual mechanical properties of the current C-Drone material. This study will run a structural analysis of the current C-Drone design and run topology optimisation on the current C-Drone structure for weight reduction using the software SolidWorks. To achieve the objectives of this project, the topology optimisation focuses on the main body of the C-Drone structure. Before the optimisation can be done, the input of material properties needs to be defined beforehand. The mechanical properties of the Aluminium 6061 were obtained from experimental data which involved the tensile test and flexural test of the material. These values are inserted into the simulation software, SolidWorks and structural analysis for the current design. From this analysis, the critical part or area caused by the loads and internal stress were determined. From the result obtained, in order to ensure the weight is reduce without reducing the structural rigidity, the area is excluded from part removal for the topology optimisation. The topology process runs the analysis again if the results from the optimisation show the structure is unable to withstand the total load. The best results have been obtained from the series of simulations and they show the suggestion for the most suitable modification strategy. It also shows the comparison of the current design of body structure C-Drone by the software SolidWorks. The result of the stress, deformation, displacement, and safety of factors of the construction is within acceptable limits. From this study, it can be concluded that the current design of body structure C-Drone is overdesigned because when the support of the current body structure C-Drone has been discarded, the result is still in the range of yield strength.